Neurological Soft Signs in Obsessive Compulsive Disorder: Standardised Assessment and Comparison with Schizophrenia - D. Bolton; W. Gibb; A. Lees; P. Raven; J. A. Gray; E. Chen; R. Shafran (Behavioural Neurology)
While several studies have detected raised levels of neurological soft signs in patients with obsessive compulsive disorder (OCD), the specificity of these abnormalities remains uncertain. This study used a new standardised measure, the Cambridge Neurological Inventory (CNI), to assess soft signs in 51 subjects with OCD. Comparison was made with data on patients with schizophrenia and a non-clinical control group from a previously reported study. Individuals with OCD showed raised levels of soft signs compared with non-clinical controls in many categories of the CNI: Motor Coordination, Sensory Integration, Primitive Reflexes, Extrapyramidal Signs, and Failure of Suppression. Compared with patients with schizophrenia, the OCD group had lower levels of neurological signs in some CNI categories: Hard Signs, Motor Co-ordination, Tardive Dyskinesia, Catatonic Signs, and Extrapyramidal Signs. However, levels of soft signs in the OCD group did not significantly differ from those in the schizophrenia group in other CNI categories: Sensory Integration, Primitive Reflexes and Failure of Suppression. The significance of these patterns of findings is discussed.